Typescript: writing safe and expressive code - Shevchenko, B. M. (ХНУРЕ, 2019)
According to many ratings, JavaScript is the most popular programming language in the world. JavaScript has achieved such popularity due to its simplicity, flexibility, and expressiveness. However, it has significant disadvantages including dynamic weak typing and excessive liberty. That is why transpilers were developed - programs, that transform code from the language of choice to JavaScript. TypeScript is a definitive winner in the world of transpilers. “TypeScript is a typed superset of JavaScript that compiles to plain JavaScript.”, as the official website says [1]. TypeScript makes writing code easier, but still, there exist subtle problems that can be solved by a proper approach to coding.